Neurosteroid allopregnanolone (3α,5α-THP) inhibits inflammatory signals induced by activated MyD88-dependent toll-like receptors - Balan, Irina (Transl Psychiatry, 2021)
We have shown that endogenous neurosteroids, including pregnenolone and 3α,5α-THP inhibit toll-like receptor 4 (TLR4) signal activation in mouse macrophages and the brain of alcohol-preferring (P) rat, which exhibits innate TLR4 signal activation. The current studies were designed to examine whether other activated TLR signals are similarly inhibited by 3α,5α-THP. We report that 3α,5α-THP inhibits selective agonist-mediated activation of TLR2 and TLR7, but not TLR3 signaling in the RAW246.7 macrophage cell line. The TLR4 and TLR7 signals are innately activated in the amygdala and NAc from P rat brains and inhibited by 3α,5α-THP. The TLR2 and TLR3 signals are not activated in P rat brain and they are not affected by 3α,5α-THP. Co-immunoprecipitation studies indicate that 3α,5α-THP inhibits the binding of MyD88 with TLR4 or TLR7 in P rat brain, but the levels of TLR4 co-precipitating with TRIF are not altered by 3α,5α-THP treatment. Collectively, the data indicate that 3α,5α-THP inhibits MyD88- but not TRIF-dependent TLR signal activation and the production of pro-inflammatory mediators through its ability to block TLR-MyD88 binding. These results have applicability to many conditions involving pro-inflammatory TLR activation of cytokines, chemokines, and interferons and support the use of 3α,5α-THP as a therapeutic for inflammatory disease.